Estimation of Water Use Efficiency and Economics of Potato Varieties under different Methods of Irrigation - Dey, Joy Kumar; Ray, Lala I. P. (International Journal of Economic Plants, 2017)
The study was conducted during November, 2015 to April 2016 in the research farm of College of Post-graduate Studies, Central Agricultural University, Umiam, Meghalaya, India. The experiment was done under split plot design (SPD) with tree replications and the potato was planted in flat bed by maintaining a spacing of 50×20 cm2 in a plot size of 4×3 m2 to find out water use efficiency (WUE) and economics (gross return, net return, benefit cost ratio) of the potato varieties under different irrigation methods, where, three different irrigation methods viz., furrow irrigation (I1), Micro-sprinkler irrigation (I2) and Gravity-fed drip irrigation (I3) as a main plot treatments and four different varieties viz., Kufri Jyoti (V1), Kufri Megha (V2), Kufri Giriraj (V3) and Kufri Giridhari (V4) as sub-plot treatments. From the experiment it was found that the highest WUE was recorded under Gravity-fed drip irrigation (I3) but was at par with the Micro-sprinkler irrigation (I2), among the varieties it was for Kufri Megha (V2) but was at par with Kufri Jyoti (V1) and Kufri Giriraj (V3). In terms of economics, highest gross return, net return and benefit cost ratio (BCR) was recorded under Gravity-fed drip irrigation (I3) but it was at par with Micro-sprinkler irrigation (I2), among the varieties highest gross return, net return and BCR was recorded under variety Kufri Megha, which was at par with the varieties Kufri Jyoti (V1) and Kufri Giriraj (V3).